1996
DOI: 10.1111/j.1745-4557.1996.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Stability of Potato Chips Fried in Canola, Partially Hydrogenated Canola, Soybean and Cottonseed Oils

Abstract: The effect of four oils, canola (CO), soybean (SBO), cottonseed (CSO) and partially hydrogenated canola (PHCO) on sensory and instrumental attributes ofpotato chips were determined afer a modified Schaal oven test (S) storage for 0, 6, and 12 days at 60C and practical (P) storage for 18 weeks at 23C. At time 0, CO and CSO chips had higher characteristic potato chip odor/favor and lower off odor/favor than other chips. Frying oils did not affect characteristic potato chip odorflavor and off odor at S6 and S12. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…For $8 and S 16 chips, no differences in L values as a result of oil treatment were found. In contrast, researchers (10,12) have reported that potato chips darkened on storage. At $8 chips fried in CO, PHS, and PHC had significantly lower a values (were less red) than the HR, but did not differ in redness from other chips which were similar and like the HR.…”
Section: Resultsmentioning
confidence: 91%
“…For $8 and S 16 chips, no differences in L values as a result of oil treatment were found. In contrast, researchers (10,12) have reported that potato chips darkened on storage. At $8 chips fried in CO, PHS, and PHC had significantly lower a values (were less red) than the HR, but did not differ in redness from other chips which were similar and like the HR.…”
Section: Resultsmentioning
confidence: 91%
“…Different types of vegetable, partially hydrogenated or blends of oils are used for deep fat frying. 6 Important characteristics for selecting frying oils are high oxidative stability, high smoke point, low foaming, low melting point, bland avor, availability, nutritional value, and cost. 5 Most common frying oils in the potato chip industry come from corn, canola, sunower (mid oleic and high oleic variants), high oleic (HO) safflower and cottonseed oils.…”
Section: Introductionmentioning
confidence: 99%
“…5 Most common frying oils in the potato chip industry come from corn, canola, sunower (mid oleic and high oleic variants), high oleic (HO) safflower and cottonseed oils. 6 Although partially hydrogenated oil improves resistance to rancidity, it is being phased out due to trans fat health concerns by consumers. 7 A preference for blended vegetable oils over a sole type is due to economic purposes, an improved resistance to oxidation and a longer shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…This attribute did not affect the acceptability of potato snacks as it stayed unchanged. No significant colour intensity changes were detected by Hawrysh et al (1996) and Pangloli et al (2002) during storage of potato chips, although this attribute is very important for consumers in their quality assessment (Pedreschi et al, 2012). Decreased ratings for flavour (resulting from the decomposition of hydroperoxidesthe primary oxidation products) and loss of crispness (due to water gain) were expected because potato snacks that had been stored for two months contained an increased level of…”
Section: Resultsmentioning
confidence: 99%